Posyandu PTM-DM terhadap Terkendalinya DM pada Penyandang DM Tipe II di Wilayah Puskesmas Gamping II, Sleman - Induniasih Induniasih; Wahyu Ratna (POLTEKKES KEMENKES YOGYAKARTA, 2016)
Diabetus mellitus (DM) is a group of metabolic diseases characterized by increased blood sugar levels. This disease as a result of an unhealthy lifestyle such as overeating, eating fatty foods, lack of activity, stress and heredity. WHO estimates that global prevalence of type II diabetes will increase from 171 million in 2000 to 366 million in 2030, and Indonesia ranked fourth. The Objective of the study is knowing the in?uence of PTM - DM Posyandu toward controlled diabetes in people with type II diabetes in Puskesmas Gamping II. This study is a Quasi type experiment with pre-test and post-test design with control group. At this design the experimental group made a preliminary selection in the form of pre-test that checks blood sugar levels during the (observation 1) prior to the intervention of the ministry in Posyandu PTM - DM (X) is then carried out post - test were similar (observation 2). The results of the sample 32 in the intervention group gained an increase in the category of being 16% to 22%, while the control group category was decreased from 13% to 6%. In the category of bad in the intervention group from 62% to 59%, while the control group category of bad 59% to 69%. Using the Mann Whitney test in the intervention group showed p = 0.031, meaning there in?uence posyandu PTM-DM controlled with DM. There is in?uence between Posyandu PTM-DM against controlled diabetes in people with Type II diabetes mellitus.